Catalytic Co-Cracking of Used Cooking Oil Methyl Ester and Polystyrene Waste for Gasoline-Rich Biofuel Over Mesoporous Al-MCM-41 Catalyst - Nurfitriyah, Arifah; Assari, Anas; Pamungkas, Firman Satria; Elliyanti, Ardita; Darmawan, Ahmad Hawky; Juwono, Hendro (IPTEK Journal of Proceedings Series, 2020)
Used cooking oil and packaging foam are typical waste materials that are abundantly available as household and fast food restaurant waste with high energy content, thus representing potential feedstock for conversion into an alternative energy source. In this study, catalytic co-cracking was examined at 300°C in atmospheric pressure to generate fuel products with gasoline-like properties from a mixture of used cooking oil biodiesel and polystyrene pyrolysis oil. Mixture of ceramic powder and Al-MCM-41 was used as catalyst in comparison to a pristine mesoporous aluminosilicate material. The product distribution of produced biofuel wes analyzed by gas chromatography – mass spectrometry. Experimental results exhibit that catalytic co-cracking process generated up to 64,6 – 67,2% yield of liquid hydrocarbon. The product distribution and the quality of the resulting biofuel were significantly affected by Si/Al ratio of the catalyst. Pristine Al-MCM-41 with lower Si/Al ratio was more favored for the enrichment of gasoline range fraction (C7–C12) which give 88,98% yield, while Al-MCM-41/ceramic with higher Si/Al ratio only give 32,84% yield of gasoline fraction. Moreover, lower oxygenate compound with better stability of biofuel was also obtained using pristine Al-MCM-41 catalyst. The produced biofuel blend by both catalysts indicated promising physical properties including higher calorific value (53,2 and 52,4 MJ/kg) and higher-octane number (RON 99,8 and 95,5) than commercial gasoline.